Assessment of Effect of Treatments against Frost in Young Plantations of Tectona grandis Linn. F., Acacia nilotica (Linn.) Willd. Ex Del. and Azadirachta indica A. Juss. in Plains of Punjab - Luna, R. K.; Kumar, Vijay (Indian Forester, 2008)
One to three years old plantations of Tectona grandis (Teak), Acacia nilotica (Kikar) and Azadirachta indica (Neem) were subjected to seven treatments in the frost affected areas from October 2004 to March 2005. The assessment of percentage damage was made by measuring the height loss in the affected plants. The results indicate that Tectona grandis was the most affected species producing 15.81% damage and the Azadirachta indica the least (4.83%). Among the treatments T2 (irrigation after 15 days interval during frost period) was found the best giving the least damage percentage (4.08) followed by T3 (application of NPK fertilizer) giving 4.91% damage. The results indicate the traditional measures such as covering of plants with thatching grass (kullies) and polythene bags were not effective. The results also found that in Teak and Kikar, the damage increased from Ist to IIIrd year whereas in Neem, it decreased. The method described in the experiment can be reliably used in the field to assess the damage due to frost. Height / diameter ratio can also be used to gauge the propensity of frost damage and thus to take advance silvicultural operations in time.